Miniaturized Mechanical Antennas: Advances, Challenges, and Future Directions - Hao Ren (Advanced Physics Research)
Abstract In the past decade, miniaturized mechanical antennas have become a research focus. Several types of mechanical antennas based on different operation principles, including mechanical antennas based on magnetoelectric effect, mechanical antennas based on permanent magnets, mechanical antennas based on electrets, and mechanical antennas based on piezoelectric resonators, are presented, all with sizes significantly smaller than conventional electrical antennas operating at the same resonant frequencies. This review focuses on the advances in mechanical antennas, potential applications as well as challenges and potential future directions for further performance improvement. Although the sizes of the state‐of‐the‐art mechanical antennas are several orders of magnitude smaller than traditional electrical counterparts with the same resonant frequencies, the reported maximum operation distance of mechanical antennas is still short, which is a major challenge for it to be widely implemented. By adopting new materials for mechanical antennas, adopting array configurations, adopting receiving antennas with higher sensitivity, and building new electromagnetic‐electromechanical coupled simulation methods, the maximum operation distance may be significantly improved, making mechanical antennas widely implemented in the Internet of Things (IoT), wireless sensor networks (WSN), implantable medical devices (IMD), and portable electronics applications.